ANALISIS PROBLEMATIKA PUSTAKAWAN DAERAH KABUPATEN MAJENE DALAM MENINGKATKAN MINAT BACA MASYARAKAT MAJENE - Ridwan, Muhammad Ridwan (Istiqra: jurnal hasil penelitian, 2025)
The Reading interest index in Indonesia is very low, at only 0.001%, meaning that only one person out of every thousand residents is considered an avid reader. One way to respond to this data is to improve the Reading infrastructure within the community, such as by ensuring librarians have the explicit knowledge needed regarding library facilities. The purpose of this research is to analyze the issues faced by librarians in increasing reading interest among the people of Majene. This type of research is descriptive. The approach used is qualitative. Data sources consist of primary and secondary data. Data was collected through observation, interviews, and documents. Data were analyzed using the principles of Miles and Huberman, which comprise three methods: data reduction, data presentation, and conclusion. The research findings indicate that librarians in enhancing people’s reading interest in Majene face several comprehensive problems, including limited facilities and infrastructure, a lack of book collections that meet user needs, low public Reading interest, and insufficient strategies for socializing library services. As a practical implication of this research, the local government needs to place greater emphasis on libraries by allocating a larger budget to procure book collections, improve facilities and infrastructure, and train librarians.